Further exploration of the heterocyclic diversity accessible from the allylation chemistry of indigo - Shakoori, Alireza; Bremner, John B.; Abdel-Hamid, Mohammed K.; Willis, Anthony C.; Haritakun, Rachada; Keller, Paul A. (Beilstein Journal of Organic Chemistry, 2015)
Diversity-directed synthesis based on the cascade allylation chemistry of indigo, with its embedded 2,2’-diindolic core, has resulted in rapid access to new examples of the hydroxy-8a,13-dihydroazepino[1,2-a:3,4-b']diindol-14(8H)-one skeleton in up to 51% yield. Additionally a derivative of the novel bridged heterocycle 7,8-dihydro-6H-6,8a-epoxyazepino[1,2-a:3,4-b']diindol-14(13H)-one was produced when the olefin of the allylic substrate was terminally disubstituted. Further optimisation also produced viable one-pot syntheses of derivatives of the spiro(indoline-2,9'-pyrido[1,2-a]indol)-3-one (65%) and pyrido[1,2,3-s,t]indolo[1,2-a]azepino[3,4-b]indol-17-one (72%) heterocyclic systems. Ring-closing metathesis of the N,O-diallylic spiro structure and subsequent Claisen rearrangement gave rise to the new (1R,8aS,17aS)-rel-1,2-dihydro-1-vinyl-8H,17H,9H-benz[2',3']pyrrolizino[1',7a':2,3]pyrido[1,2-a]indole-8,17-(2H,9H)-dione heterocyclic system.
Keywords: allylation; cascade reactions; indigo; nitrogen heterocycles; rearrangement